QALBU DALAM PANDANGAN AL-GHAZALI - Anin Lihi, Duriana (JURNAL MEDIASI, 2018)
This research is about the concept Qalbu in the view of al-Ghazali. The subject matter is what is meant by al-Ghazali’s hearts as well as how it functions on the formation of human personality. The discussion is seen to approach history and mysticism and discussed using literature study with descriptive qualitative analysis. Based on the results of the study found that Qalbu according to alGhazali, is the container and the center of the human body, he who ruled the body to do anything he wants. Qalbu is something subtle (al-Lathiifah) and smooth it is the essence of man which is related to the subtle human nature, that he felt anxiety and happiness. If the heart of a good, it will better the entire human body. There are four potential influence hearts, namely: Fu’aad, Sadr, Eve and Nafs, each of which has its own function and the potential to do something. Qalbu can serve to form the human personality well if the heart and four potential influence hearts are located on the territory of taqwa is the approach yourself and always called and given the (remembrance) to Allah., The human personality is formed properly depending on how the net hearts it from nature- charasteristic deplorable and diseases be contagious